(untitled) (The Research of Medical Science Review, 2025)
Microneedle (MN) patches have emerged as a groundbreaking advancement in transdermal drug delivery, offering a minimally invasive, painless, and efficient alternative to conventional hypodermic injections. These patches consist of micron-scale needles that penetrate the outermost layer of the skin to facilitate drug absorption while avoiding deeper tissues, thus reducing pain and needle-associated risks. Microneedle patches have shown significant promise in vaccine delivery, transdermal drug administration, and cosmetic applications due to their ability to enhance patient compliance, eliminate the need for trained medical personnel, and minimize biohazardous waste. Different types of microneedles, including solid, coated, dissolving, and hydrogel-forming microneedles, have been developed to optimize drug delivery efficiency. These innovations address challenges such as bioavailability, stability, and sustained release, making them particularly beneficial for self-administration and mass immunization programs. Recent studies have highlighted the successful use of microneedle patches for delivering vaccines against infectious diseases, such as influenza and COVID-19, with enhanced immunogenic responses. Additionally, microneedle patches have been explored for pain management, hormone therapy, and cancer treatment, demonstrating improved therapeutic outcomes. Despite their numerous advantages, challenges such as large-scale manufacturing, regulatory approval, and cost-effectiveness remain significant hurdles to widespread adoption. Innovations in biomaterials, nanotechnology, and 3D printing are expected to further refine microneedle technology, increasing its efficacy and accessibility. The future of microneedle patches lies in the development of smart, responsive systems integrated with biosensors for real-time monitoring of drug release and patient response. This review provides a comprehensive analysis of microneedle patches, their mechanisms, applications, advantages, challenges, and future prospects in drug delivery and vaccine administration.